Poverty, Privilege, and Political Dynamics Within Rural School Reform: Unraveling Educational Leadership in the Invisible America. (September 2016) - Mette, Ian M.; Biddle, Catharine; Mackenzie, Sarah V.; Harris-Smedberg, Kathy
This case was written to help prepare teacher-leaders, principals, and central office administrators, particularly those in rural and economically marginalized settings, who are expected to lead teachers and stakeholders in their community through increasingly stressed economic conditions. The intent of the case study is for educators to examine the impact privilege has on the often White, middle-class mind-set of educators, particularly when supporting economically marginalized communities. Educators studying this case should examine the role that poverty, privilege, and politics play in school leadership, specifically when thinking about school reform and community improvement efforts.